Factors associated with urinary tract infection in the early phase after performing intermittent catheterization in individuals with spinal cord injury: a retrospective study - Xing, Huayi; Dai, Hongyue; Li, Baohua; Yuan, Xiaoning; Liu, Xiaoxuan; Cui, Guoqing; Liu, Nan; Biering-Sørensen, Fin (Frontiers in Medicine, 2023)
Objectives: To investigate the occurrence rate of urinary tract infections (UTIs) in the early phase after starting intermittent catheterization (IC), and to explore the possible factors associated with UTIs after starting IC among people with spinal cord injury (SCI). Setting: An inpatient rehabilitation department of a teaching hospital in China. Design: Retrospective chart review. Methods: A chart review was performed for traumatic and non-traumatic SCI patients who started IC during their inpatient stay. Demographic information, comorbidity of diabetes, urine analysis results before IC, method of IC (sterile or clean), use of bladder irrigation, cessation of IC and its reasons, and UTI events were collected. Results: 183 adult individuals were included. 60 (32.8%) were female. Median age was 49.0 years. Median time post injury was 2 months. The overall occurrence rate of UTI after performing IC was 1.31 (95% confidence interval: 0.96-1.77) events per 100 days. 69 (37.7%) discontinued IC during hospitalization, and UTIs was leading reason of cessation (50.7%). Female sex, use of antibiotics for infections other than UTI, and use of bladder irrigation were found associated with lower occurrence rate of UTI in the early phase after starting IC, with an odds ratio of 0.38 (P=0.019), 0.20 (P=0.022) and 0.24 (P<0.001), respectively. Conclusions: UTI after starting IC is not uncommon among people with SCI. The study indicated that antibiotic prophylaxis and routine bladder irrigation might be associated with reduction of UTI in the early phase after starting IC. Further research is needed to provide more evidences.